A new, easily miniaturized steerable endoscope. - Breedveld, P.
This article describes a new steerable endoscope for laparoscopic surgery. The steerable mechanism was inspired by the tentacles of squid and consists only of standard parts such as cables, coil springs, rings, and tubes. Laparoscopic surgery is carried out using an endoscope and long and slender instruments that are inserted through small incisions in the abdominal wall. The endoscope contains a light source and a camera that displays a picture of the abdominal cavity on a monitor in the operation room. The surgeon uses the instruments to carry out the operation while estimating the spatial position of the instruments and the organs from the camera picture. The mechanism can be easily miniaturized to a very small diameter, making it suitable for low-cost mass production of steerable endoscopes, instruments, and catheters. A patent for the mechanism has been applied for, and it is currently being commercialized.
Keywords: Abdominal cavity; Abdominal wall; Catheters; Instruments; Laparoscopic surgery; Light source; Low-cost mass production; Miniaturized steerable endoscope; Organs; Squid